Pathway analysis of vegetable farming commercialization - Mariyono, Joko; Kuntariningsih, Apri; Dewi, Hanik A.; Latifah, Evi; Daroini, Putu B.; Negoro, Aria A.; Afari-sefa, Victor; Luther, Greg (Economic Journal of Emerging Markets, 2017)
High-valued vegetable farming can increase farmers’ income if the vegetables are cultivated in commercial manner. This paper analyzes factors that determine farmers’ intention to commercialize vegetable farming; and the effect of commercialization on farmers’ income. The study used structural equation model to estimate paths affecting farmers to engage commercial farming and its impact of commercial on households’ income. Household and farm characteristics, business environment, and market support were hypothesized to influence farmers to commercialize vegetable farming. Data for this study were compiled from a quantitative survey of 360 farm households located in four major vegetable producing regions of Eastern Indonesia. Results indicate that commercial vegetable farming provides economic advantage in terms of increased income. To encourage commercial vegetable farming, vegetable agribusiness terminal with all market infrastructures should be established in the potential vegetable producing regions of Indonesia.